Prognostic value of phosphorylated STAT3 in advanced rectal cancer: a study from 104 French patients included in the EORTC 22921 trial. Issue 10 (27th September 2010) - Monnien, Franck; Zaki, Harouna; Borg, Christophe; Mougin, Christiane; Bosset, Jean-François; Mercier, Mariette; Arbez-Gindre, Francine; Kantelip, Bernadette
Abstract : Background: Signal transducer and activator of transcription 3 (STAT3) has been implicated as an oncogene in several neoplastic diseases. However, the biological effects of STAT3 have not been extensively studied in rectal carcinogenesis. Aims: To evaluate STAT3 activation in advanced rectal cancers and its association with clinicopathological variables and prognosis. Methods: Nuclear immunohistochemical expression of phosphorylated STAT3 (p-STAT3) was studied in 104 advanced rectal cancers (T3–T4). All patients were participating in the EORTC 22921 trial to assess whether preoperative chemoradiotherapy followed by postoperative chemotherapy improved overall and progression-free survival. Results: Nuclear p-STAT3 expression was detected in 37.5% of rectal cancer patients. No correlation was observed between p-STAT3 and any clinicopathological variables tested. However, patients with tumours positive for p-STAT3 had significantly improved overall survival. Conclusion: These results highlight an unexpected role for nuclear p-STAT3 expression in advanced rectal cancers and need further investigation to clarify this finding.